2000
DOI: 10.1034/j.1600-0668.2000.010001027.x
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a Sink-Diffusion Model to Describe the Interaction between Volatile Organic Compounds (VOCs) and Material Surfaces

Abstract: A sink-diffusion model to describe the interaction between material surfaces and volatile organic compounds (VOCs) in indoor air has been introduced. The model is based on adsorption/desorption on the material surfaces and diffusion into the materials. Test chamber experiments with exposure of nylon carpet and polyvinyl chloride (PVC) covering against alpha-pinene and toluene were used to validate the model and to make comparisons with a sink model based on the Langmuir adsorption isotherm. The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…C at m/z 262, but lower-abundance CHA cluster ions complexed with HSO 4 and ZnCl 3 were also observed at m/z 297 and 369, respectively. These clusters show that CHA is most likely bound to these anionic species at atmospheric conditions, since the high vacuum conditions of both SIMS instruments would preclude formation of the ions by ion-molecule reactions in the gas phase during analysis.…”
Section: (No 3 ]mentioning
confidence: 77%
“…C at m/z 262, but lower-abundance CHA cluster ions complexed with HSO 4 and ZnCl 3 were also observed at m/z 297 and 369, respectively. These clusters show that CHA is most likely bound to these anionic species at atmospheric conditions, since the high vacuum conditions of both SIMS instruments would preclude formation of the ions by ion-molecule reactions in the gas phase during analysis.…”
Section: (No 3 ]mentioning
confidence: 77%
“…Several approaches have combined simple models that consider neither filtration nor adsorption (Jetter & Whitfield, 2005) with more complex models that consider internal and external filtration, adsorption and desorption onto surfaces, and internal diffusion into materials (Jørgensen et al, 2000). These models can be classified into four categories:…”
Section: General Modelmentioning
confidence: 99%
“…Several studies have investigated variations in temperature and found that low temperatures favor adsorption (Van Der Wal et al, 1998;Zhang, Zhang, & Chen, 2003). Jørgensen, Dokka, and Bjørseth (2000) introduced a sink-diffusion model based on adsorption and desorption on, and diffusion into materials. They validated the model using experimental a-pinene and toluene concentrations in a chamber with two types of carpet.…”
Section: Introductionmentioning
confidence: 99%
“…Some have developed isotherms to model the partitioning into a surface (Jorgensen et al 2000). But it has not been established whether a chemical partitions primarily onto the surface of a material (Won et al 2001), or whether the compounds diffuse into the pores and/or body of the material (Cox et al 2001).…”
Section: Treatment Of Surfacesmentioning
confidence: 99%
“…Jorgensen et al proposed three general criteria for developing models of surfaces-(i) models should be based on sound physical/chemical description of the process (i.e., theoretically derived models are preferred over empirical models), (ii) models should be mathematically as simple as possible, and (iii) the model should "adequately" fit measured data (Jorgensen et al 2000). In order to best comply with these criteria, we base our model on fugacity.…”
Section: Treatment Of Surfacesmentioning
confidence: 99%